Autoecologia do lagarto Anotosaura vanzolinia (squamata: gymnophthalmidade) em àrea de caatinga no estado da Paraíba, nordeste do Brasil. - Oliveira, Bruno Halluan Soares de (2014)
The objectives this study were analyze aspects of the natural history of populations of the lizard Gymnophthalmidae Anotosaura vanzolinia present in Paraíba, through information about microhabitat, morphology, diet, and reproduction. The data used this study are samples from Forest Park Complexo Aluízio Campos and a forest located in the district São José da Mata, both in Paraíba. Sampling was conducted monthly from March-April, July-August 2011 and May 2013 to June 2014, using pitfall traps and active searching diurnal, from 08.00 to 17.00, where we analyzed the microhabitat use, air temperature and substrate and solar incidence. Individuals were collected in shaded environments, found mainly buried in the soil, confirming its fossorial behavior. Their diet consisted mainly of soil insects, being termites and ants the most important prey for their feed. Ants were more important for juveniles, which showed niche breadth significantly greater than adults. The species showed sexual dimorphism in size and body shape, with females larger snout-vent lengths than males. Its reproduction occurs during rainy season, with hatchling emerging at the end of the rainy season and early dry season, with average snout-vent length 18.85 ± 0.44 mm. The clutch size is fixed to two eggs per pregnant female and they deposit more than clutch during breeding season.